Perfluoroalkyl Substances (PFASs) in the North Sea, its tributaries and the Xiaoqing River in China - Franziska Heydebreck; Jianhui Tang; Zhiyong Xie; Ralf Ebinghaus (PANGAEA, 2015)
The production and use of long-chain perfluoroalkyl substances (PFASs) must comply with national and international regulations. Driven by increasingly stringent regulations, their production has been outsourced to less regulated countries in Asia. In addition, the fluoropolymer industry started to use fluorinated alternatives, such as 2,3,3,3-tetrafluoro-2-(1,1,2,2,3,3,3-heptafluoropropoxy)propanoic acid (HFPO-DA). Between August 2013 and September 2014, we investigated the occurrence and distribution of HFPO-DA and legacy PFASs in surface waters of the following river/estuary systems: the Elbe and Rhine Rivers in Germany, the Rhine-Meuse delta in The Netherlands, and the Xiaoqing River in China. Distinct differences were revealed among the study areas; notably, the Chinese samples were highly polluted by an industrial point source discharging mainly perfluorooctanoic acid (PFOA). This particular point source resulted in concentrations more than 6000 times higher than an industrial point source observed in the Scheur River, where HFPO-DA was the dominant compound with a concentration of 73.1 ng/L. Moreover, HFPO-DA was detected in all samples along the coastline of the North Sea, indicating that the compound may be transported from the Rhine-Meuse delta into the German Bight via the water current. To the best of our knowledge, the fluorinated alternative, HFPO-DA, was detected for the first time in surface waters of Germany and China.
Supplement to: Heydebreck, F et al. (2015): Alternative and Legacy Perfluoroalkyl Substances: Differences between European and Chinese River/Estuary Systems. Environmental Science & Technology, 49(14), 8386-8395, https://doi.org/10.1021/acs.est.5b01648